Electrically controllable smart window with greyscale based on polymer-stabilised cholesteric texture films. Issue 12 (25th September 2016) - Fuh, Andy Ying-Guey; Shin, Zong Bai; Yang, Ching Han; Wu, Shing-Trong
ABSTRACT: The study reports a novel liquid crystal (LC) film that can be applied on the transmissive substrates or stuck on existing casement window to upgrade the shield. The shadow area and transmittance can be adjusted according to the condition of the outer sunshine. The window is energy saving for which maintains the transmittance after a once-off operation of pulse amplitude modulation (PAM) electric driving. Such a film can be applied in smart curtain, display frame edge and other transmissive electro-optical devices. GRAPHICAL ABSTRACT: